Preparation method of bio-based aromatic hydrocarbon
By using FER structural sheet crystalline molecular sieve catalyst with specific morphology, the problems of insufficient mass transfer performance and poor carbon deposit resistance in the preparation of bio-aryl aromatic hydrocarbons are solved, and efficient and stable bio-aryl aromatic hydrocarbon preparation and recycling performance are achieved.
Patent Information
- Application Number
- CN202310714505.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-17
AI Technical Summary
The prior art has problems such as insufficient mass transfer performance, poor carbon deposit resistance, poor cycle stability and easy loss of active sites when preparing bio-based aromatic hydrocarbons, which is difficult to meet the needs of industrial applications.
The flake crystal molecular sieve with a FER structure with a specific morphology is used as a catalyst. The biomass-based raw materials and ethylene are converted into bio-based aromatic hydrocarbons through Diels-Alder cycloaddition and dehydration reaction. The catalyst has good mass transfer properties and resistance to carbon deposits. Capacity and cyclic stability.
The efficient preparation of bio-based aromatic hydrocarbons is achieved, the conversion rate and selectivity are improved, and the catalyst remains stable in multiple cycles, reducing the cost of catalyst replacement.
Smart Images

Figure CN119143561A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic chemistry, and in particular to a method for preparing bio-based aromatic hydrocarbons. Background Art
[0002] In recent years, the use of catalytic conversion of biomass resources to prepare bio-based chemicals has received more and more attention and research. Aromatic compounds benzene, toluene and para-xylene (PX) are very important bulk chemicals. Benzene can be used as an upstream product to produce downstream products such as alkylbenzene and phenol; toluene; toluene can not only be used as a solvent, but also as a chemical intermediate to prepare other chemicals through chlorination or sulfonation reactions; para-xylene (PX) can be used to prepare terephthalic acid, which is further used to prepare polyethylene terephthalate (PET) polyester. The annual demand for PX in the world has reached more than 50 million tons. If bio-based aromatics can be developed to replace traditional petrochemical aromatics, it will be of great significance. For example, several bio-based PX pathways have been reported so far, among which the most promising one is to use biomass-derived 2,5-dimethylfuran (DMF) as a raw material and react with ethylene to prepare PX through Diels–Alder addition and dehydration reactions under the catalysis of solid acid.
[0003] DMF and ethylene first undergo Diels–Alder cycloaddition reaction to generate cycloaddition intermediates. Further, the cycloaddition intermediates undergo ring-opening dehydration aromatization under the catalysis of acid to generate PX and water. US20140296600A1 reported that H-type molecular sieves were used as catalysts to catalyze this reaction to prepare PX. When HY molecular sieves were used as catalysts, the PX selectivity reached 75%, and when H-Beta molecular sieves were used as catalysts, the PX selectivity reached 90%. Both of these molecular sieves have three-dimensional structures, and have insufficient diffusion performance for reactions that are prone to carbon deposition, and serious alkylation side reactions are prone to occur in the super cage of HY. In the process of preparing PX from DMF and ethylene, the oligomerization of reactant molecules or the condensation reaction of the intermediate product 2,5-hexanedione (HDO) are prone to cause serious carbon deposition problems. US20190344252A1 reports that a completely de-Alized Beta molecular sieve modified with phosphorus is used to prepare PX by the reaction of DMF and ethylene. This type of catalyst has undergone a modification process, and the active sites are no longer the Al carried by the molecular sieve itself. Instead, the loaded P active sites are easily lost and have poor stability, making it difficult to meet the requirements for recycling. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of insufficient mass transfer performance, poor carbon deposition resistance, poor cycle stability, easy loss of active sites, etc. in the preparation of bio-based aromatics in the prior art, and to provide a method for preparing bio-based aromatics.
[0005] During the research, the inventors of the present invention found that in the preparation of bio-based aromatics, a three-dimensional molecular sieve is generally used as a catalyst to catalyze the catalytic reaction of biomass-based raw materials with ethylene to obtain bio-based aromatic products. However, it was found that the three-dimensional molecular sieve catalyst has insufficient mass transfer performance, poor carbon deposition resistance, or poor catalyst cycle stability, and easy loss of active sites when used in the reaction, which brings challenges to practical industrial applications. There is no report on the use of a two-dimensional layered molecular sieve for the catalytic reaction of biomass-based raw materials with ethylene to prepare bio-based aromatic products.
[0006] Based on the above research, the first aspect of the present invention provides a method for preparing bio-based aromatic hydrocarbons, which comprises: in the presence of a catalyst and optionally a solvent, a biomass-based furan compound and / or a biomass-based ketone compound raw material reacts with ethylene to form a DA reaction and a dehydration reaction; wherein the catalyst comprises a molecular sieve having a FER structure, and the molecular sieve has a flaky crystal structure. Among the total number of crystals counted, the flaky crystals with a thickness of no more than 10 nm account for no less than 70%.
[0007] The second aspect of the present invention provides a method for preparing bio-based aromatic hydrocarbons on the basis of the first aspect of the present invention, wherein the preparation method of the molecular sieve comprises: forming a gel mixture from raw materials containing a silicon source, an aluminum source, an alkali source, a structure directing agent and water for crystallization reaction, then roasting the solid product obtained by the crystallization reaction to obtain molecular sieve raw powder, and finally exchanging the molecular sieve raw powder with ammonium and heat treating to obtain the molecular sieve; the structure directing agent has a structure as shown in formula (1): In formula (1), X is OH or halogen.
[0008] Through the above technical scheme, the present invention adopts a catalyst including a molecular sieve with a FER structure having a specific morphology, which can efficiently convert bio-based aromatics. The conversion rate of biomass-based raw materials and the selectivity of bio-based aromatic products are both very high, and the catalyst has good mass transfer performance, which is conducive to the rapid and smooth progress of the reaction and has strong resistance to carbon deposition. It has excellent cyclic stability performance, the active sites can remain without loss after several cycles of use, and the reaction performance can remain unchanged, which is conducive to long-term operation in large-scale reactions and saves the cost of replacing catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 is the XRD spectrum of the molecular sieve product in Example 1;
[0010] Figure 2 is a SEM picture of the molecular sieve in Example 1;
[0011] Figure 3 is a SEM picture of the molecular sieve in Example 6;
[0012] Figure 4 is the XRD pattern of the Na-type FER molecular sieve in Comparative Example 1;
[0013] Figure 5 This is the SEM electron microscope image of the molecular sieve sample in Comparative Example 1. DETAILED DESCRIPTION
[0014] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0015] In the present invention, the structure of the molecular sieve is obtained by X-ray diffraction (XRD) spectrum analysis, wherein the X-ray diffraction (XRD) spectrum is obtained on a Panalytical X PERPRO X-ray powder diffractometer using a CuKα ray source.
[0016] In the present invention, the SiO2 / Al2O3 molar ratio of the molecular sieve is obtained by testing its element content, which is measured by a Varian 725-ES inductively coupled plasma atomic emission spectrometer (ICP). The molecular sieve catalyst sample is digested with hydrofluoric acid, and the element content is measured in moles.
[0017] In the present invention, the internal and external specific surface areas of the molecular sieve are measured on a Micromeretic ASAP2020M physical adsorption instrument, the sample is degassed at 350°C for 4 hours, and the full-pore test method is used. The total specific surface area of the sample is obtained by the BET five-point method, and the external specific surface area is calculated by the t-plot model.
[0018] In the present invention, the crystal morphology of the molecular sieve is obtained on the S-4800II instrument through a scanning electron microscope (SEM) photograph; wherein during the test, an observation field is randomly selected, and the average value of the sum of the lengths and the average value of the sum of the thicknesses of all the lamellar crystals in the observation field are calculated, and the test is repeated 10 times. At the same time, the percentage of the total number of crystals in the observation field with a thickness of no more than 10 nm (for example, no more than 10 nm, 9 nm, 8 nm) is counted and calculated. In the present invention, the length is defined as the largest dimension of the lamellar crystal size, the width is defined as the second largest dimension of the lamellar crystal size, and the thickness is defined as the smallest dimension of the lamellar crystal size. Therefore, the width is not calculated during the test.
[0019] A first aspect of the present invention provides a method for preparing bio-based aromatic hydrocarbons, which comprises: in the presence of a catalyst and optionally a solvent, a biomass-based furan compound and / or a biomass-based ketone compound raw material and ethylene undergo a reaction including a DA reaction and a dehydration reaction; wherein the catalyst comprises a molecular sieve having a FER structure, the molecular sieve having a flaky crystal structure, and in the total number of crystals counted, the flaky crystals having a thickness of no more than 10 nm account for no less than 70%.
[0020] In the present invention, the term "DA reaction" refers to a Diels-Alder cycloaddition reaction.
[0021] In the present invention, a molecular sieve including a FER structure is used as a catalyst to prepare bio-based aromatics, which can not only catalyze the conversion of biomass-based raw materials into corresponding bio-based aromatics with high selectivity, but also the catalyst has excellent mass transfer performance and excellent multiple recycling performance.
[0022] According to the present invention, in some embodiments, the SiO2 / Al2O3 molar ratio of the molecular sieve is 22 to 45. By adopting the above-mentioned embodiments, biomass-based raw materials can be more efficiently converted into corresponding bio-based aromatics.
[0023] According to the present invention, in some preferred embodiments, the SiO2 / Al2O3 molar ratio of the molecular sieve is 22-35. By adopting the aforementioned embodiment, biomass-based raw materials can be more efficiently converted into corresponding bio-based aromatics.
[0024] According to the present invention, in some preferred embodiments, the SiO2 / Al2O3 molar ratio of the molecular sieve is 22 to 30. With the aforementioned embodiments, the conversion rate of biomass-based raw materials and the selectivity of bio-based aromatics are both very high.
[0025] According to the present invention, in some embodiments, the specific surface area of the molecular sieve is 350-550m 2 By adopting the above-mentioned implementation mode, the catalyst has good mass transfer performance, which is conducive to the rapid and smooth progress of the reaction.
[0026] According to the present invention, in some embodiments, the external specific surface area of the molecular sieve is not less than 120m 2 / g, for example, 120m 2 / g, 150m 2 / g, 160m 2 / g, 170m 2 / g, 200m 2 / g, 228m 2 / g or 240m 2 / g, and the range consisting of any two of the above values. By adopting the above-mentioned embodiment, the mass transfer performance of the raw material on the outer surface of the molecular sieve is better, and the anti-carbon deposition ability is stronger, and a high reaction rate can be maintained.
[0027] According to the present invention, the specific surface area of the molecular sieve refers to the sum of the external specific surface area and the internal specific surface area. In some preferred embodiments, based on the specific surface area of the molecular sieve, the external specific surface area of the molecular sieve accounts for no less than 30%, for example, 30%, 38%, 40%, 45%, 46% or 50%, and the range composed of any two of the above values. By adopting the above-mentioned embodiment, the mass transfer performance of the raw material on the outer surface of the molecular sieve is better, and the anti-carbon deposition ability is stronger, and a high reaction rate can be maintained. At the same time, the bio-based aromatics also have high selectivity, and the catalyst has excellent cyclic stability.
[0028] According to the present invention, in some embodiments, the total pore volume of the molecular sieve is 0.80-1.50 cm 3 According to the above-mentioned embodiment, the biomass-based raw material has good diffusivity on the catalyst and can maintain a high reaction rate.
[0029] According to the present invention, in some embodiments, the mesopore volume of the molecular sieve is 0.50-1.30 cm 3 / g, preferably 0.60-1.30cm 3 By adopting the above-mentioned embodiment, the biomass-based raw material has good diffusivity on the catalyst, and has stronger resistance to carbon deposition, can maintain a high reaction rate, and the catalyst has excellent cycle stability.
[0030] According to the present invention, in some embodiments, the molecular sieve has a flaky crystal structure. In the present invention, biomass-based raw materials are particularly suitable for carrying out the catalytic reaction of the present invention under the aforementioned embodiment of the molecular sieve including the FER structure different from the prior art, and the mass transfer performance of the raw materials is better, and the carbon deposition resistance is stronger, and a high reaction rate can be maintained, while the corresponding bio-based aromatics also have high selectivity, and the catalyst has excellent cyclic stability.
[0031] According to the present invention, in some embodiments, the average thickness of the plate-like crystals is not greater than 13 nm, for example, 1 nm, 2 nm, 3 nm, 5 nm, 8 nm, 11 nm, 12 nm or 13 nm, and a range consisting of any two of the above values, preferably 3-13 nm. Using the above embodiments, the raw material has a high conversion rate, the bio-based aromatics have a high selectivity, and the catalyst has excellent cyclic stability.
[0032] According to the present invention, in some embodiments, the average length of the plate-like crystals is not greater than 80 nm, for example, 30 nm, 40 nm, 60 nm, 70 nm, 75 nm or 80 nm, and a range consisting of any two of the above values, preferably 30-80 nm. Using the above embodiments, the raw material has a high conversion rate, the bio-based aromatics have a high selectivity, and the catalyst has excellent cyclic stability.
[0033] According to the present invention, it can be understood that bio-based aromatic hydrocarbons refer to corresponding aromatic hydrocarbons prepared from biomass-based raw materials. Those skilled in the art can use corresponding raw materials according to the actual required bio-based aromatic hydrocarbons. In some embodiments, the furan compounds include one or more of furan, 2-methylfuran, and 2,5-dimethylfuran.
[0034] According to the present invention, in some embodiments, the ketone compound includes 2,5-hexanedione.
[0035] According to the present invention, it can be understood by those skilled in the art that when a biomass-based raw material is used to carry out a catalytic reaction including a DA reaction and a dehydration reaction with ethylene, when the biomass-based raw material is furan, its corresponding target bio-based product is benzene; when the biomass-based raw material is 2-methylfuran, its corresponding target bio-based product is toluene; when the biomass-based raw material is 2,5-dimethylfuran, its corresponding target bio-based product is p-xylene; when the biomass-based raw material is 2,5-hexanedione, its corresponding target bio-based product is p-xylene. In the present invention, those skilled in the art can use the corresponding biomass-based raw material according to the bio-based aromatics actually required.
[0036] In the present invention, "optionally solvent" means that the catalytic reaction of the present invention including DA reaction and dehydration reaction can be carried out in the presence of a solvent or without a solvent. In some embodiments, when a solvent is present, the concentration of the raw material in the solvent is not less than 10 wt %. The above-mentioned embodiment is conducive to increasing the reaction rate, improving the efficiency and reducing the energy consumption.
[0037] According to the present invention, in some preferred embodiments, the concentration of the raw material in the solvent is not less than 15wt%, preferably 15-30wt%. By adopting the aforementioned embodiment, while increasing the reaction rate, improving the efficiency and reducing the energy consumption, the yield of the target product bio-based aromatics can also be increased.
[0038] According to the present invention, in some embodiments, when a solvent is present, the solvent comprises an aprotic organic solvent. Using the above embodiments, the raw material has a high conversion rate and the bio-based aromatic hydrocarbon has a high selectivity.
[0039] According to the present invention, in some preferred embodiments, the aprotic organic solvent is selected from one or more of n-hexane, cyclohexane, n-heptane, n-octane and tetrahydrofuran.
[0040] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the catalyst is not particularly limited. In some embodiments, the mass ratio of the raw material to the catalyst is 4-20:1, preferably 6-15:1.
[0041] According to the present invention, ethylene is a gas. When the reaction is carried out, ethylene is charged into the reaction system to react with the raw materials. As long as the purpose of the present invention can be achieved, there is no special limitation on the charging pressure of the ethylene. The higher the ethylene pressure and the greater the concentration, the higher the reaction rate. However, considering the comprehensive reaction rate and the pressure resistance of the reaction container, in some embodiments, the ethylene is pressurized to 1-6MPa, preferably 2-4MPa.
[0042] According to the present invention, those skilled in the art can understand that a certain reaction temperature is required when carrying out the catalytic reaction of the present invention including the DA reaction and the dehydration reaction. When the reaction temperature is above 200°C, the reaction can occur faster. Considering the pressure resistance and high temperature resistance of conventional material reactors, the conditions of the catalytic reaction are not particularly limited. In some embodiments, the conditions of the catalytic reaction include: the reaction temperature is 220-320°C, preferably 240-280°C.
[0043] According to the present invention, in some embodiments, the conditions of the catalytic reaction include: the reaction time is 3-24h, preferably 6-12h.
[0044] Ammonium exchange is the process of using ammonium ions to exchange the alkali metal atoms (such as Na atoms) connected to the O adjacent to Al in the molecular sieve framework with NH4 ions in the solution, converting the molecular sieve into NH4 + type, and then through a heat treatment (such as drying, calcining) operation, it is finally converted into an H-type molecular sieve. Because the present invention has been calcined to remove the structure-directing agent before ammonium exchange to form a molecular sieve raw powder, and then the molecular sieve raw powder is used for ammonium exchange and heat treatment to only make an H-type molecular sieve with a certain acid amount, which has no effect on the specific surface area, pore volume, SiO2 / Al2O3 molar ratio, structure and crystal structure morphology and other characteristics of the molecular sieve raw powder; therefore, on the basis of the fact that the structure-directing agent has been removed by calcination and the molecular sieve raw powder has been formed, the present invention directly characterizes the specific surface area, pore volume, SiO2 / Al2O3 molar ratio, structure and crystal structure morphology and other characteristics of the molecular sieve raw powder. The specific surface area, pore volume, SiO2 / Al2O3 molar ratio, structure and crystal structure morphology and other characteristics of the H-type molecular sieve prepared from the molecular sieve raw powder are the same as those of the corresponding molecular sieve raw powder.
[0045] In the present invention, the molecules with FER structure prepared by the present invention are used as catalysts for the catalytic reactions including DA reaction and dehydration reaction in the present invention. The catalyst has good mass transfer performance, is conducive to the rapid and smooth progress of the reaction and has strong anti-carbon deposition ability; and such molecular sieves with FER structure have excellent cycle stability performance, the active sites can remain unchanged after several cycles of use, the reaction performance can remain unchanged, which is conducive to long-term operation in scale-up reactions and saves the cost of replacing catalysts.
[0046] According to the present invention, in some preferred embodiments, in formula (1), X is OH. With the above embodiments, the feedstock has a high conversion rate, the bio-based aromatics has a high selectivity, and the catalyst has excellent cycle stability.
[0047] In the present invention, the method for forming a gel mixture from "raw materials containing silicon source, aluminum source, alkali source, structure directing agent and water" is not particularly limited. For example, the raw materials including silicon source, aluminum source, alkali source, structure directing agent and water are stirred at room temperature (15-35°C) for 2-8 hours to obtain a gel mixture.
[0048] According to the present invention, the solid product obtained by the crystallization reaction is the intermediate product required by the present invention. There is no special limitation on the method for obtaining the solid product in the present invention. Those skilled in the art can achieve it according to conventional methods in the art, such as filtering, washing (such as water washing) and drying the reaction solution obtained after the crystallization reaction; wherein, the drying can be selected under vacuum conditions or under normal pressure conditions (such as drying in an oven at 80-110°C overnight (8-12h)).
[0049] According to the present invention, as long as the purpose of the present invention can be achieved, the calcination conditions are not particularly limited, for example, the calcination temperature is 350-700° C., and the calcination time is 2-7 hours.
[0050] According to the present invention, as long as the purpose of the present invention can be achieved, ammonium exchange can be carried out according to conventional means in the art, such as exchanging ammonium ions between molecular sieve raw powder and an aqueous solution containing ammonium ions, then centrifuging and washing, and repeating the above steps 2-5 times to obtain a solid sample for heat treatment; wherein the temperature during ammonium exchange can be 50-70°C.
[0051] According to the present invention, the dosage of molecular sieve raw powder and aqueous solution containing ammonium ions can be selected as needed. For example, the mass ratio of molecular sieve raw powder to aqueous solution containing ammonium ions is 1:(10-30), and the concentration of aqueous solution containing ammonium ions can be 0.1-0.5 mol / L.
[0052] According to the present invention, the heat treatment method is to convert ammonium ions into H, which can be carried out according to conventional methods in the art, such as drying and then calcining, wherein the drying can be done at 80-120°C overnight, and the calcination can be done at 350-700°C for 2-7 hours.
[0053] According to the present invention, in some embodiments, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the alkali source is calculated as OH - The molar ratio of the silicon source, aluminum source, alkali source, structure directing agent and water is 1: 0.021-0.045: 0.25-0.35: 0.07-0.14: 10-50, preferably 1: 0.022-0.044: 0.26-0.33: 0.08-0.14: 10-50. By adopting the above-mentioned embodiment, the raw material has a high conversion rate, the bio-based aromatic hydrocarbon has a high selectivity, and the catalyst has excellent cycle stability.
[0054] According to the present invention, in some embodiments, the silicon source comprises silica sol. According to the above embodiments, the raw material has a high conversion rate, the bio-based aromatic hydrocarbon has a high selectivity, and the catalyst has excellent cycle stability.
[0055] The silica sol in the present invention can be obtained commercially, and is a dispersion of nano-scale silica particles in water. The present invention has no special limitation on the content of silica in the silica sol, and for example, the content may be 20-50 wt%. In the embodiments of the present invention, a silica sol with a silica content of 40 wt% is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.
[0056] According to the present invention, in some embodiments, the aluminum source includes sodium aluminate. Using the above embodiments, the raw material has a high conversion rate, the bio-based aromatics has a high selectivity, and the catalyst has excellent cycle stability.
[0057] According to the present invention, in some embodiments, the content of Al2O3 in the sodium aluminate is 38-43% by weight (for example, 38%, 39%, 40.5%, 41%, 42% or 43%, and the range consisting of any two of the above values), and the content of Na2O is 30-33% by weight (for example, 30%, 30.6%, 31%, 32% or 33%, and the range consisting of any two of the above values).
[0058] According to the present invention, the sodium aluminate sold on the market is generally industrial-grade sodium aluminate. For cost considerations, industrial-grade sodium aluminate is generally used for experiments. Industrial-grade sodium aluminate often contains hydration water. It can be understood that the content of Al2O3 in the sodium aluminate of the present invention is 38-43% by weight, the content of Na2O is 30-33% by weight, and the balance is water.
[0059] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the crystallization treatment are not particularly limited. In some embodiments, the conditions of the crystallization treatment include: a crystallization temperature of 140-180°C.
[0060] According to the present invention, in some embodiments, the conditions of the crystallization treatment include: the crystallization time is 2-8 days.
[0061] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:
[0062] The chemical components in the reaction solution were qualitatively analyzed by gas chromatography-mass spectrometry (GC-MS) and quantitatively analyzed by gas chromatography (GC), and the conversion rate of the raw materials and the yield of the reaction products were calculated; the GC-MS model was Agilent 7890A (Agilent, USA), equipped with a Wax polar capillary column, and the GC model was Agilent 7890B, equipped with a hydrogen ion flame detector (FID) and a Wax polar capillary column.
[0063] In the present invention, based on the molar amount of the substance in the reaction solution detected by GC, the conversion rate formula of the raw material 2,5-dimethylfuran (DMF) or 2,5-hexanedione (HDO) is:
[0064] Conversion rate (%) of DMF (and / or HDO) = (molar amount of DMF (and / or HDO) consumed in the reaction) / (molar amount of DMF (and / or HDO) initially added) × 100%.
[0065] The product PX selectivity calculation formula is:
[0066] Selectivity of product PX (%) = (molar amount of PX produced by the reaction) / (molar amount of DMF (and / or HDO) consumed in the reaction)×100%.
[0067] Example 1
[0068] 0.5 g of catalyst (H-type nano FER molecular sieve), 3.0 g of 2,5-dimethylfuran and 17.0 g of n-heptane were added to a high-pressure reactor, and 3.5 MPa of ethylene was charged. The temperature was raised with magnetic stirring and the reaction was carried out at 250°C for 12 hours. After the reaction was completed and cooled, the reaction liquid was filtered, and the conversion rate of the raw material 2,5-dimethylfuran (DMF) and the selectivity of the product p-xylene (PX) were calculated by gas chromatography.
[0069] The preparation method of H-type nano FER molecular sieve is as follows:
[0070] 17.24 g of deionized water, 0.612 g of sodium aluminate (containing 40.5 wt % of Al2O3, 30.6 wt % of Na2O, and the balance being water), 0.780 g of sodium hydroxide, 3.58 g of trimethylethylammonium hydroxide aqueous solution (containing 25.00 wt % of trimethylethylammonium hydroxide) and 12.78 g of silica sol (containing 40.0 wt % of SiO2) were stirred at room temperature for 4 hours to obtain a gel mixture;
[0071] The gel mixture was placed in a stainless steel reactor with a polytetrafluoroethylene liner, and heated at 170°C and 20 rpm for crystallization for 3 days; after the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve product;
[0072] The XRD spectrum of molecular sieve products is as follows: Figure 1 As shown, through Figure 1 It can be determined that the product is a molecular sieve with FER structure; the SiO2 / Al2O3 molar ratio of this molecular sieve measured by ICP is 34.8; the SEM picture of the molecular sieve is as follows Figure 2 As shown in the figure, it can be seen that the molecular sieve crystals have a flaky crystal structure. The average length of the flaky crystals is 80nm, the average thickness of the flaky crystals is 12nm, and the flaky crystals with a thickness of no more than 10nm account for 70% of the total crystals. The specific surface area of the molecular sieve measured by the BET method is 489m 2 / g, external specific surface area is 177m 2 / g; total pore volume 1.10cm 3 / g, and the mesopore volume is 0.97cm 3 / g;
[0073] The molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, and then centrifuged and washed. The above steps were repeated twice, and the obtained sample was dried at 100°C overnight, and calcined in air at 550°C for 4 hours to obtain an extremely thin H-type nano FER molecular sieve. The total acid content of the molecular sieve was measured by NH3-TPD to be 1178 μmol / g.
[0074] The conversion rate of 2,5-dimethylfuran (DMF) was 91.5%, and the selectivity of the product p-xylene (PX) was 87.1%.
[0075] Example 2
[0076] The method according to Example 1 is different in that:
[0077] The preparation method of H-type nano FER molecular sieve is as follows:
[0078] 13.80 g of deionized water, 0.431 g of sodium aluminate (containing 40.5 wt % of Al2O3, 30.6 wt % of Na2O, and the balance being water), 0.457 g of sodium hydroxide, 2.60 g of trimethylethylammonium hydroxide aqueous solution (containing 25.00 wt % of trimethylethylammonium hydroxide) and 7.72 g of silica sol (containing 40.0 wt % of SiO2) were stirred at room temperature for 4 hours to obtain a gel mixture;
[0079] The gel mixture was placed in a stainless steel reactor with a polytetrafluoroethylene liner, and heated at 160°C and 30 rpm for crystallization for 6 days; after the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve product;
[0080] XRD diagram of molecular sieve products Figure 1 Similarly, it can be determined that the product is a molecular sieve with FER structure; the SiO2 / Al2O3 molar ratio of the molecular sieve measured by ICP is 30.4; the SEM electron microscope image of the sample is Figure 2 Similarly, the molecular sieve crystals have a flaky crystal structure. The average length of the flaky crystals is 75nm, the average thickness is 12nm, and the flaky crystals with a thickness of no more than 10nm account for 75% of the total crystals. The BET method measures the specific surface area of the molecular sieve to be 506m 2 / g, external specific surface area 228m 2 / g; total pore volume 1.35cm 3 / g, and the mesopore volume is 1.21cm 3 / g;
[0081] The molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, and then centrifuged and washed. The above steps were repeated twice, and the obtained sample was dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain an extremely thin H-type nano FER molecular sieve sample. The total acid content of the molecular sieve was measured by NH3-TPD to be 1291 μmol / g.
[0082] The conversion rate of 2,5-dimethylfuran (DMF) was 93.8%, and the selectivity of the product p-xylene (PX) was 87.8%.
[0083] Example 3
[0084] The method according to Example 1 is different in that:
[0085] The preparation method of H-type nano FER molecular sieve is as follows:
[0086] 32.46 g of deionized water, 0.806 g of sodium aluminate (containing 40.5 wt % of Al2O3, 30.6 wt % of Na2O, and the balance being water), 0.642 g of sodium hydroxide, 4.71 g of trimethylethylammonium hydroxide solution (containing 25.00 wt % of trimethylethylammonium hydroxide) and 12.02 g of silica sol (containing 40.0 wt % of SiO2) were stirred at room temperature for 4 hours to obtain a gel mixture;
[0087] The gel mixture was placed in a stainless steel reactor with a polytetrafluoroethylene liner, and heated at 170°C and 20 rpm for crystallization for 5 days; after the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve product;
[0088] XRD diagram of molecular sieve products Figure 1 Similarly, it can be determined that the product is a molecular sieve with FER structure; the SiO2 / Al2O3 molar ratio of the molecular sieve measured by ICP is 25.2; the SEM electron microscope image of the sample is similar to Figure 2 Similarly, the molecular sieve crystals have a flaky crystal structure. The average length of the flaky crystals is 75nm, the average thickness is 11nm, and the flaky crystals with a thickness of no more than 10nm account for 75% of the total crystals. The specific surface area of the molecular sieve measured by the BET method is 513m 2 / g, external specific surface area 191m 2 / g, total pore volume 1.39cm 3 / g, and the mesopore volume is 1.23cm 3 / g.
[0089] The molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, and then centrifuged and washed. The above steps were repeated twice, and the obtained sample was dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain an extremely thin H-type nano FER molecular sieve sample. The total acid content of the molecular sieve was measured by NH3-TPD to be 1354 μmol / g.
[0090] The conversion rate of 2,5-dimethylfuran (DMF) was 92.5%, and the selectivity of the product p-xylene (PX) was 89.2%.
[0091] Example 4
[0092] The method according to Example 1 is different in that:
[0093] The preparation method of H-type nano FER molecular sieve is as follows:
[0094] 29.93 g of deionized water, 0.687 g of sodium aluminate (containing 40.5 wt % of Al2O3, 30.6 wt % of Na2O, and the balance being water), 0.497 g of sodium hydroxide, 3.28 g of trimethylethylammonium hydroxide aqueous solution (containing 25.00 wt % of trimethylethylammonium hydroxide) and 9.01 g of silica sol (containing 40.0 wt % of SiO2) were stirred at room temperature for 4 hours to obtain a gel mixture;
[0095] The gel mixture was placed in a stainless steel reactor with a polytetrafluoroethylene liner, and heated at 160°C and 30 rpm for 7 days for crystallization; after the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve product;
[0096] XRD diagram of molecular sieve products Figure 1 Similarly, it can be determined that the product is a molecular sieve with FER structure; the SiO2 / Al2O3 molar ratio of the molecular sieve measured by ICP is 22.5; the SEM electron microscope image of the sample is similar to Figure 2 Similarly, the molecular sieve crystals have a flaky crystal structure. The average length of the flaky crystals is 70nm, the average thickness is 11nm, and the flaky crystals with a thickness of no more than 10nm account for 80% of the total crystals. The BET method measures the specific surface area of the molecular sieve to be 515m 2 / g, external specific surface area 196m 2 / g, total pore volume 1.31cm 3 / g, and the mesopore volume is 1.19 cm 3 / g;
[0097] The molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, and then centrifuged and washed. The above steps were repeated twice, and the obtained sample was dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain an extremely thin H-type nano FER molecular sieve sample. The total acid content of the molecular sieve was measured by NH3-TPD to be 1457 μmol / g.
[0098] The conversion rate of 2,5-dimethylfuran (DMF) was 90.5%, and the selectivity of the product p-xylene (PX) was 90.6%.
[0099] Example 5
[0100] The method according to Example 1 is different in that:
[0101] The preparation method of H-type nano FER molecular sieve is as follows:
[0102] 10.61 g of deionized water, 0.420 g of sodium aluminate (containing 40.5 wt % of Al2O3, 30.6 wt % of Na2O, and the balance being water), 0.618 g of sodium hydroxide, 2.65 g of trimethylethylammonium hydroxide solution (containing 25.00 wt % of trimethylethylammonium hydroxide) and 10.51 g of silica sol (containing 40.0 wt % of SiO2) were stirred at room temperature for 4 hours to obtain a gel mixture;
[0103] The gel mixture was placed in a stainless steel reactor with a polytetrafluoroethylene liner, and heated and crystallized at 150°C and 30 rpm for 7 days; after the crystallization, it was filtered, washed with water, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve product;
[0104] XRD diagram of molecular sieve production Figure 1 Similarly, it can be determined that the product is a molecular sieve with FER structure; the SiO2 / Al2O3 molar ratio of the molecular sieve measured by ICP is 42.5; the SEM electron microscope image of the sample is Figure 2 Similarly, the molecular sieve crystals have a flaky crystal structure. The average length of the flaky crystals is 75nm, the average thickness is 12nm, and the flaky crystals with a thickness of no more than 10nm account for 75% of the total crystals. The BET method measures the specific surface area of the molecular sieve to be 475m 2 / g, external specific surface area 168m 2 / g, total pore volume 1.37cm 3 / g, and the mesopore volume is 1.21cm 3 / g.
[0105] The molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, and then centrifuged and washed. The above steps were repeated twice, and the obtained sample was dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain an extremely thin H-type nano FER molecular sieve sample. The total acid content of the molecular sieve was measured by NH3-TPD to be 1287 μmol / g.
[0106] The conversion rate of 2,5-dimethylfuran (DMF) was 91.8%, and the selectivity of the product p-xylene (PX) was 87.6%.
[0107] Example 6
[0108] The method according to Example 1 is different in that:
[0109] When preparing H-type nano FER molecular sieve: sodium aluminate (containing 50.6 wt% Al2O3, 40.1 wt% Na2O, and the balance being water) was used to replace the sodium aluminate in Example 1, and the content of each substance was controlled so that the feed ratio was the same as that in Example 1. The XRD pattern of the obtained molecular sieve product is Figure 1 Similarly, it can be determined that the product is a molecular sieve with FER structure; the SiO2 / Al2O3 molar ratio of the molecular sieve measured by ICP is 35.8; the SEM electron microscope image of the sample is as follows Figure 3 As shown in the figure, it can be seen that the molecular sieve crystals are in the form of long strips of flake crystal structure. The average length of the flake crystals is 95nm, the average thickness is 15nm, and the flake crystals with a thickness of no more than 10nm account for 70% of the total crystals. The specific surface area of the molecular sieve measured by BET method is 441m 2 / g, external specific surface area 103m 2 / g; total pore volume 0.36cm 3 / g, and the mesopore volume is 0.21cm 3 / g;
[0110] The molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, and then centrifuged and washed. The above steps were repeated twice, and the obtained sample was dried at 100°C overnight and calcined in air at 550°C for 4 hours to obtain a molecular sieve with a FER structure. The total acid content of the molecular sieve was measured by NH3-TPD to be 1046 μmol / g.
[0111] The conversion rate of 2,5-dimethylfuran (DMF) was 75.8%, and the selectivity of the product p-xylene (PX) was 67.2%.
[0112] Example 7
[0113] 0.5 g of catalyst (same as Example 4), 3.0 g of 2,5-hexanedione (HDO) and 17 g of n-heptane were added to a high-pressure reactor, filled with 3.0 MPa of ethylene, stirred and heated to 250° C. and reacted at 250° C. for 12 h. The reaction liquid was analyzed by gas chromatography to obtain a 2,5-hexanedione conversion rate of 97.5% and a para-xylene selectivity of 89.6%.
[0114] Example 8
[0115] 0.5 g of catalyst (same as Example 4), 3.0 g of furan and 17 g of n-heptane were added to a high-pressure reactor, filled with 3.0 MPa of ethylene, stirred and heated to 250° C. and reacted at 250° C. for 12 h. The reaction liquid was analyzed by gas chromatography to obtain a furan conversion of 97.5% and a benzene selectivity of 38.7%.
[0116] Example 9
[0117] 0.5 g of catalyst (same as Example 4), 3.0 g of 2-methylfuran and 17 g of n-heptane were added to a high-pressure reactor, filled with 3.0 MPa of ethylene, stirred and heated to 250° C. and reacted at 250° C. for 12 h. The reaction liquid was analyzed by gas chromatography to obtain a 2-methylfuran conversion rate of 94.2% and a toluene selectivity of 67.5%.
[0118] Example 10
[0119] 1.5 g of catalyst (same as Example 4) and 22.5 g of DMF were added to a high-pressure reactor, filled with 4.0 MPa of ethylene, stirred and heated to 250° C. and reacted at 250° C. for 12 h. The reaction liquid was analyzed by gas chromatography to obtain a DMF conversion rate of 80.5% and a PX selectivity of 85.9%.
[0120] Embodiment 11
[0121] 0.3 g of catalyst (same as Example 4), 3.0 g of 2,5-hexanedione (HDO) and 17.0 g of tetrahydrofuran were added to a high-pressure reactor, filled with 2.0 MPa of ethylene, stirred and heated to 320° C. and reacted at 320° C. for 3 h. The reaction liquid was analyzed by gas chromatography and the HDO conversion rate was calculated to be 98.1%, and the para-xylene selectivity was 88.7%.
[0122] Example 12
[0123] 0.3 g of catalyst (same as Example 4), 3.0 g of DMF and 17.0 g of tetrahydrofuran were added to a high-pressure reactor, filled with 3.0 MPa of ethylene, stirred and heated to 280° C. and reacted at 280° C. for 6 h. The reaction liquid was analyzed by gas chromatography to obtain a DMF conversion rate of 92.3% and a PX selectivity of 89.6%.
[0124] Embodiment 13
[0125] 0.5 g of catalyst (same as in Example 4), 3.0 g of DMF and 17.0 g of n-heptane were added to a high-pressure reactor, and 3.5 MPa of ethylene was charged. The temperature was raised with magnetic stirring and the reaction was carried out at 250° C. for 12 h. After the reaction was completed and cooled, the reaction liquid was filtered, and the conversion rate of the raw material 2,5-dimethylfuran and the selectivity of the product p-xylene were calculated by gas chromatography. The solid catalyst was recovered, calcined in an air environment at 550° C. for 6 h for regeneration and put into the next cycle.
[0126] It was determined that after one cycle, the DMF conversion rate was 90.5% and the PX selectivity was 90.6%.
[0127] When the number of cycles was 2, the DMF conversion was 90.2% and the PX selectivity was 90.7%;
[0128] When the number of cycles was 3, the DMF conversion was 89.8% and the PX selectivity was 90.4%;
[0129] When the number of cycles was 4, the DMF conversion was 90.1% and the PX selectivity was 90.6%;
[0130] After 5 cycles, the DMF conversion was 89.9% and the PX selectivity was 90.5%.
[0131] Comparative Example 1
[0132] The method according to Example 1 is different in that:
[0133] The preparation method of the molecular sieve having the FER structure is as follows:
[0134] Take 15.02g silica sol (containing 40.0 wt% SiO2), 0.76g sodium aluminate (containing 40.5 wt% Al2O3, 30.6 wt% Na2O, the balance is water), 1.98g cyclohexylamine, 0.50g NaOH, 26.99g H2O and mix; then transfer the above mixture to a stainless steel hydrothermal synthesis reactor with a polytetrafluoroethylene lining, crystallize at 160°C for 7 days at a speed of 20rpm, then centrifuge, wash with deionized water to obtain a solid product, dry it in an oven at 100°C overnight, and then calcine at 550°C for 6h to obtain a traditional Na-type FER molecular sieve. The XRD pattern of the traditional Na-type FER molecular sieve is as follows: Figure 4 As shown, it shows that the traditional FER molecular sieve has good crystallization. The SiO2 / Al2O3 molar ratio of the molecular sieve measured by ICP is 34.2. The SEM electron microscope image of the molecular sieve sample is as follows Figure 5As shown in the figure, it can be seen that the molecular sieve crystals have a flaky crystal structure. The average length of the flaky crystals is 400nm, the average thickness of the flaky crystals is 20nm, and the nano-flaky crystals with a thickness of no more than 10nm account for 30% of the total crystal count. The specific surface area of the molecular sieve measured by BET is 333m 2 / g, external specific surface area 20m 2 / g; total pore volume 0.21cm 3 / g, and the mesopore volume is 0.08cm 3 / g;
[0135] The conventional Na-type FER molecular sieve was subjected to ammonium ion exchange with a 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, followed by centrifugal washing. The above steps were repeated twice to obtain a sample which was dried overnight at 100°C and calcined in air at 550°C for 4 hours to obtain a conventional H-type FER molecular sieve sample. The total acid content of the molecular sieve was measured by NH3-TPD to be 1387 μmol / g.
[0136] The conversion rate of 2,5-dimethylfuran (DMF) was 21.5%, and the selectivity of the product PX was 39.3%.
[0137] It can be seen from the results of the examples and comparative examples that in the method for preparing bio-based aromatics of the present invention, the catalyst includes a molecular sieve with a specific flaky crystal structure, which can achieve higher conversion rate and selectivity.
[0138] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing bio-based aromatics, It is characterized in that The preparation method comprises: in the presence of a catalyst and optionally a solvent, a biomass-based furan compound and / or a biomass-based ketone compound raw material and ethylene undergo a catalytic reaction including a DA reaction and a dehydration reaction; The catalyst comprises a molecular sieve with a FER structure, and the molecular sieve has a flaky crystal structure. Among the total number of crystals counted, the flaky crystals with a thickness of no more than 10 nm account for no less than 70%.
2. The preparation method according to claim 1, in, The SiO molecular sieve 2 / Al 2 O 3 The molar ratio is 22-45, preferably 22-35, more preferably 22-30; and / or The specific surface area of the molecular sieve is 350-550m 2 / g; and / or The external specific surface area of the molecular sieve is not less than 120m 2 / g, based on the specific surface area of the molecular sieve, preferably the external specific surface area of the molecular sieve accounts for no less than 30%.
3. The preparation method according to claim 1 or 2, in, The total pore volume of the molecular sieve is 0.80-1.50cm 3 / g; The mesopore volume of the molecular sieve is 0.50-1.30cm 3 / g, preferably 0.60-1.30cm 3 / g.
4. The preparation method according to any one of claims 1 to 3, in, The average thickness of the plate-like crystals is not greater than 13 nm; and / or The average length of the plate-like crystals is not more than 80 nm.
5. The preparation method according to any one of claims 1 to 4, in, The furan compound includes one or more of furan, 2-methylfuran, and 2,5-dimethylfuran; and / or The ketone compound includes 2,5-hexanedione.
6. The preparation method according to any one of claims 1 to 5, in, When a solvent is present, the concentration of the raw material in the solvent is not less than 10 wt %, preferably not less than 15 wt %, more preferably 15-30 wt %; and / or The solvent comprises an aprotic organic solvent, and preferably the aprotic organic solvent is selected from one or more of n-hexane, cyclohexane, n-heptane, n-octane and tetrahydrofuran.
7. The preparation method according to any one of claims 1 to 6, in, The mass ratio of the raw material to the catalyst is 4-20:1, preferably 6-15:1; and / or The ethylene is pressurized to 1-6MPa, preferably 2-4MPa; and / or The conditions of the catalytic reaction include: The reaction temperature is 220-320°C, preferably 240-280°C; and / or The reaction time is 3-24h, preferably 6-12h.
8. A preparation method according to any one of claims 1 to 7, in, The preparation method of the molecular sieve comprises: forming a gel mixture from raw materials containing a silicon source, an aluminum source, an alkali source, a structure directing agent and water to perform a crystallization reaction, then calcining a solid product obtained by the crystallization reaction to obtain a molecular sieve raw powder, and finally performing ammonium exchange and heat treatment on the molecular sieve raw powder to obtain the molecular sieve; wherein the structure directing agent has a structure as shown in formula (1): In formula (1), X is OH or halogen, preferably OH.
9. The preparation method according to claim 8, in, Silicon source is SiO 2 Aluminum source is Al 2 O 3 Calculation, alkali source is OH - The molar ratio of the silicon source, aluminum source, alkali source, structure directing agent and water is 1: 0.021-0.045: 0.25-0.35: 0.07-0.14: 10-50, preferably 1: 0.022-0.044: 0.26-0.33: 0.08-0.14: 10-50.
10. The preparation method according to claim 8 or 9, in, The silicon source comprises silica sol; and / or The aluminum source includes sodium aluminate, preferably Al 2 O 3 The content of Na is 38-43% by weight. 2 The content of O is 30-33% by weight; and / or The conditions of the crystallization treatment include: a crystallization temperature of 140-180° C. and / or a crystallization time of 2-8 days.
